Media Libraries in an Age of Unending Consumption: A Bottomless Pit - Van Esler, Mike (Lexington Books, 2023)
As the home video market upended traditional film industry models, media libraries emerged as important sources of ancillary revenue. The inflection point for media library exploitation came in 2007, when Netflix launched its streaming service, relying on extensive licensing of film and television libraries to grow its subscriber base. In this book, Mike Van Esler examines how media libraries and business models have evolved since the home video era, with particular emphasis placed on the streaming age of the past fifteen years. Van Esler argues that media libraries have grown beyond their usages from the pre-home video era to become central to today’s corporate media strategy. By studying the ways in which media library exploitation has scaled up since the turn of the new millennium, the author identifies insights into larger media industry trends. Ultimately, this book explores the intersection of corporate media, independent distributors, private equity, tech companies, and audiences. Scholars of media studies, business, and sociology will find this book of particular interest.